Field performance of the Determine HBsAg point-of-care test for diagnosis of hepatitis B virus co-infection among HIV patients in Zambia - Chisenga, Caroline C. (J Clin Virol, 2017)
BACKGROUND: We evaluated the field performance of a rapid point-of-care (POC) test for hepatitis B surface antigen (HBsAg) that could support decentralization and scale-up of hepatitis B virus (HBV) diagnosis in Africa. OBJECTIVE: To determine the field performance of the Determine HBsAg POC test for diagnosis of HBV co-infection among HIV patients in Zambia. STUDY DESIGN: Between 2013–2014, we screened HIV-infected adults for HBsAg at two urban clinics in Zambia. A subset were tested with the POC Determine HBsAg (Alere, USA) by finger prick in the clinic and HBsAg serology (Access2Analyzer, Beckman Coulter) at a reference laboratory. If either test was reactive, we determined HBV viral load (VL) and genotype. We described patient demographic and clinical characteristics (including liver fibrosis) and assessed the sensitivity, specificity, positive and negative predictive values (PPV and NPV) of the Determine test. In secondary analyses, we assessed sensitivity among patients with replicating HBV (i.e., VL>20 IU/ml) and with high HBV VL (i.e., >20,000 IU/ml). RESULTS: Among 412 participants with both HBsAg tests, median age was 34 years, 51% were women, and median CD4 was 208 cells/mm(3). By serology, 66 (16%) were HBsAg-positive. Overall Determine had 87.9% sensitivity, 99.7% specificity, 98.3% PPV, and 97.7% NPV. Six of 8 patients with false negative results had undetectable HBV VL and no evidence of significant liver fibrosis. Test sensitivity was 95.9% among the 51 with replicating HBV and 100% among the 28 with high HBV VL. CONCLUSIONS: Determine HBsAg is a cheaper alternative HBV testing option compared to the gold standard ELISA and has high specificity and good sensitivity in the field among HIV-infected individuals.